A Metaphorical Debugger Model to support deaf and hearing impaired in Java programming learning - Nascimento, Marcos D. do; Oliveira, Francisco C. de M. B.; Brandao, Anarosa A. F.; Silva, Lidiane C.; Queiroz, Bruno; Furtado, Eder (Proceedings - Frontiers in Education Conference, 2019)
This innovative practice full paper presents a Metaphorical Debugger Model (JAD) to support deaf and hearing impaired in the process of learning how to program in Java. In Brazil, 9.7 million people are deaf or hearing impaired (DHI). DHI people usually face several barriers to get proper education. During a series of Java classes conducted by our team, we verified that these difficulties were also related to the use of software that is not tailored for their impairment. We also saw that DHI students encountered many problems while developing and evolving their codes using the traditional tools, for instance, visual signs to perform tasks, can be difficult to understand, in addition, the high degree of abstraction required for the programming logic, can be an accessibility barrier for them. Thus, we decided to propose JAD aiming to provide accessible debugging for DHI. The JAD uses the concept of metaphorical interfaces, adopting appropriate symbols and signs borrowed from traffic to aid in the process of code debugging and evolution. In this paper, we present some user studies with JAD. The results suggest that Java programmers, DHI e non-DHI, had similar performance in task related to software evolution when JAD was used.